An interdisciplinary challenge: responsibilities in German cancer-related fatigue management from the professional and patient perspective - Wagner, Anna S.; Milzer, Marlena; Steindorf, Karen; Kiermeier, Senta; Nguyen, Truong D; Schmidt, Martina; Maatouk, Imad (The oncologist, 2025)
Objectives: Due to its complexity, the management of cancer-related fatigue (CRF) is best based on an interdisciplinary care approach. Thus, we examined the preferred and the actual distribution of responsibilities from the perspectives of healthcare professionals and patients. Materials and Methods: An online survey was conducted among physicians (N = 148), nurses (N = 184), and psycho-oncologists (N = 144) in Germany. The participants evaluated a series of statements and selected the professional disciplines that they deemed most responsible for specific tasks in CRF management. Data were complemented with the patient perspective. Experiences of cancer patients (N = 1,179) were assessed by questionnaires. Data from the healthcare professional and patient perspective were analyzed descriptively. For comparisons between professional groups, Kruskal-Wallis H tests and subsequent Dunn-Bonferroni tests were used. - Results: Healthcare professionals and patients agreed on a lack of interdisciplinary collaboration on CRF. Professionals valued the necessity of addressing CRF and educating patients, which was not mirrored in patient experiences. Physicians in aftercare and rehabilitation were overall perceived as main actors in CRF management. Nurses and psycho-oncologists frequently considered their own discipline as responsible for most of the tasks. - Conclusion: It is necessary not only to define task-related responsibilities in standardized operating procedures but to foster interprofessional collaboration in the management of CRF.
Veröffentlicht: 28 July 2025
Gesehen am 20.01.2026